Partner notification for sexually transmitted infections in developing countries: a systematic review - Vermund Sten H; Chamot Eric; Alam Nazmul; Streatfield Kim; Kristensen Sibylle (BMC, 2010)
Abstract Background The feasibility and acceptability of partner notification (PN) for sexually transmitted infections (STIs) in developing countries was assessed through a comprehensive literature review, to help identify future intervention needs. Methods The Medline, Embase, and Google Scholar databases were searched to identify studies published between January 1995 and December 2007 on STI PN in developing countries. A systematic review of the research extracted information on: (1) willingness of index patients to notify partners; (2) the proportion of partners notified or referred; (3) client-reported barriers in notifying partners; (4) infrastructure barriers in notifying partners; and (5) PN approaches that were evaluated in developing countries. Results Out of 609 screened articles, 39 met our criteria. PN outcome varied widely and was implemented more often for spousal partners than for casual or commercial partners. Reported barriers included sociocultural factors such as stigma, fear of abuse for having an STI, and infrastructural factors related to the limited number of STD clinics, and trained providers and reliable diagnostic methods. Client-oriented counselling was found to be effective in improving partner referral outcomes. Conclusions STD clinics can improve PN with client-oriented counselling, which should help clients to overcome perceived barriers. The authors speculate that well-designed PN interventions to evaluate the impact on STI prevalence and incidence along with cost-effectiveness components will motivate policy makers in developing countries to allocate more resources towards STI management.